Загальні юридичні гарантії трудових прав людини при укладенні трудового договору - Мельник, К. Ю.; Melnyk, K. Yu. (Соціальне право. - 2022. - № 1. - С. 6-16, 2022)
Розглянуто загальні юридичні гарантії трудових прав людини при укладенні трудового договору, а саме: свобода укладення трудового договору; заборона включення до трудових договорів умов, що погіршують становище працівників порівняно з чинним законодавством, колективними договорами та угодами; обов’язкове інформування працівника про умови трудового договору до початку роботи; заборона необґрунтованої відмови у прийнятті на роботу; заборона дискримінації при прийнятті на роботу; заборона вимагати від осіб, які поступають на роботу, відомостей, подання яких не передбачено законодавством; обмеження строку випробування при прийнятті на роботу та закріплення випадків, коли випробування не встановлюється; обмеження застосування строкових трудових договорів та контрактів. Наголошено на випадках порушення вказаних гарантій, що актуалізує необхідність у посиленні контролю з боку уповноважених державних органів за виконанням відповідних законодавчих норм, а також забезпечення невідворотності покарання правопорушникам та відновлення прав осіб, які зазнали порушення трудових прав при укладенні трудового договору. Надано пропозиції та рекомендації з удосконалення національного законодавства.

The article considers general legal guarantees of human labor rights when concluding an employment contract, namely: freedom to conclude an employment contract; prohibiting the inclusion in labor contracts of conditions that worsen the position of employees compared to current legislation, collective agreements and agreements; mandatory informing the employee about the terms of the employment contract before starting work; prohibition of unjustified refusal of employment; prohibition of discrimination in hiring; prohibition to demand from persons applying for work, information, the submission of which is not provided for by legislation; limitation of the probationary period upon employment and confirmation of cases when the probationary period is not established; restrictions on the use of fixed-term employment contracts and contracts. It is proven that the national labor legislation provides a sufficient number of general legal guarantees of human labor rights when concluding an employment contract for the proper provision and protection of the relevant rights. In view of the rare cases of violations of the specified guarantees in Ukraine, the need to strengthen control by authorized state bodies over the implementation of relevant legislative norms, as well as ensuring the inevitability of punishment for offenders and the restoration of the rights of persons who suffered violations of labor rights when concluding an employment contract is noted.The analysis of the norms of the Law of Ukraine "On the Organization of Labor Relations in the Conditions of Martial Law" in the field of regulation of the conclusion of labor contracts shows that they do not critically reduce the guarantees of human labor rights when concluding a labor contract, established by the national labor legislation for peacetime conditions. Proposals and recommendations for improving national legislation are provided. In particular, part 2 of Art. 22 of the Labor Code of Ukraine shall be amended as follows: "Unreasonable refusal to hire is prohibited, i.e. refusal in the presence of a vacant workplace (position) without any reasons or for reasons that do not relate to the qualification or professional qualities of an individual, or for other reasons , not provided for by law".

Рассмотрены общие юридические гарантии трудовых прав человека заключении трудового договора. Акцентировано на случаях нарушения гарантий, что актуализирует необходимость в усилении контроля со стороны уполномоченных государственных органов за исполнением соответствующих законодательных норм, а также обеспечения неотвратимости наказание правонарушителям и восстановление прав лиц, подвергшихся нарушению трудовых прав при заключении трудового договора. Представлены предложения и рекомендации по усовершенствование национального законодательства.
Keywords: трудові відносини; labor relations; трудовые отношения; трудовий договір; employment contract; трудовой договор; юридичні гарантії; legal guarantees; юридические гарантии; трудові права; labor rights; трудовые права; роботодавець; employer; работодатель; працівник; employee; работник; дискримінація; discrimination; дискриминация